The Effect of Ratio of Red Guava with Soursop and Arabic Gum Concentration on the Quality of Soft Candy - Maria Sisca Novianty Simanjuntak; Linda Masniary Lubis; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The purpose of this study was to determine the effect of ratio of red guava with soursop and arabic gum concentration on the quality of soft candy. This study used completely randomized design with two factors, ie : ratio of red guava and soursop (S) (40% : 60%, 50% : 50%, 60% : 40%, 70% : 30%) and arabic gum concentration (G) (0,5%, 1,0%, 1,5%, 2,0%). Parameters analyzed were moisture content, ash content, total soluble solid, vitamin C content, total acid, score of organoleptic values of colour, taste and texture and hedonic of organoleptic values of colour, taste and flavour. The ratio of red guava with soursop gave significant effect on moisture content, total soluble solid, vitamin C content, total acid, score of organoleptic values of colour, taste, and hedonic of organoleptic values of colour, flavour and taste. Arabic gum concentration had highly significant effect on moisture content, ash content, total soluble solid, vitamin C content, score of organoleptic values of colour, texture and hedonic of organoleptic values of colour. Interactions of the two factors had highly significant effect on moisture content and had significant effect on vitamin C content and hedonic of organoleptic values of colour. The ratio of red guava with soursop  pulps of (40% : 60%) and arabic gum concentration of (2,0%) produced the best quality of soft candy. Keywords : Arabic gum, red guava, soft candy, soursop.